EFEKTIFITAS PENYULUHAN KESEHATAN OLEH PEER GROUP DAN TENAGA KESEHATAN TENTANG PERILAKU HIDUP BERSIH SEHAT (PHBS) CUCI TANGAN BERSIH PADA SISWA SD N 01 DAN 02 BONOSARI SEMPOR KEBUMEN - Reza, faisal; -, Marsito; Wati, Rina Saras (Jurnal Ilmiah Kesehatan Keperawatan, 2012)
One effort to change behavior in health is by increasingknowledge. Increased knowledge of clean handwashing is throughcounseling. This study aims to identification issues concerning theeffectiveness of peer group counseling and counseling by health workersto the level of knowledge of clean handwashing of grader V students inSDN 1 and SDN 2 BONOSARI village district bonosari sempor Kebumen2011. This research was pre-experimental design. The research designwas used in pretest-posttest design. The population in this study is thefive-grade student at SD N 1 and SD N 2 BONOSARI in the villageBONOSARI were 30 students. And samples taken with the technique ofNon-Probability Sampling. Sampling of saturated (total sampling). Toexamine the effectiveness of counseling conducted paired t-test test usingSPSS.Statistical analysis with paired t-test test test statistics obtainedby the peer group (peer-group) with a t value <t table (0,645 <1.033) andp value 0.524 > 0.05 means there is no difference between the level ofknowledge before and after obtaining counseling about the cleanhandwashing by age group (peer-group) in SDN 1 and SDN 2 Bonosari .And from the results of statistical tests by health officials found that thevalue of the t <t table (-2,646 < 1,033) and p value 0,019 <0,05 meansthere is difference between the level of knowledge before and afterobtaining counseling about the health of clean handwashing by healthworkers in the SD N 1 dan SD N 2 Bonosari.Keywords: Counseling, peer group, health workers, the level ofknowledge.